Moisture content of root canal dentine affects detection of microcracks using micro‐computed tomography. (18th September 2017) - Rödig, T.; Müller, C.; Hoch, M.; Haupt, F.; Schulz, X.; Wiegand, A.; Rizk, M.
Abstract: Aim: To evaluate the effect of moisture content in root canal dentine on detection of microcracks using micro‐computed tomography. Methodology: Ten roots with and without craze lines or cracks (each n  =   5) were selected and scanned six times with different moisture conditions of root dentine using a micro‐CT scanner at a high resolution of 10.5 μm. Scanning conditions were as follows: (i) after 30‐day wet storage, (ii) after 2‐h dry time, (iii) after 48‐h wet storage, (iv) after 24‐h dry time, (v) after 48‐h wet storage, (vi) after 2‐h dry time. From each scan, cross‐sectional images were obtained at intervals of 1 mm (total n  =   708) and evaluated for the presence of dentinal microcracks twice by five calibrated blinded observers. Statistical analysis was performed by nonparametric analysis of variance for longitudinal data ( P  <   0.05). Results: Intra‐rater percentage agreement ranged between 92% and 98%, whereas inter‐rater percentage agreement was 81% and 83%, respectively. No significant differences between all wet groups as well as between both groups with 2‐h dry time were detected ( P  >   0.05). Almost no cracks were observed after wet storage with a significant increase of cracks after 2‐h dry time ( P  <   0.001). Significantly more microcracks were identified after 24 h than after 2‐h dry time ( P  <   0.004). Conclusions: Moisture content of dentine influenced detection of microcracks when evaluated using micro‐CT. Scanning should be performed on dried specimens to allow reliable identification of dentinal defects. Formation of new cracks during dry periods up to 24 h was disproved.